HARMONIZING THE CLASH OF SUFISM AND SHARIA IN AL GHAZALI’S THOUGH - Ahmad, Supriyadi (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2018)
Al-Ghazali is an expert and great Muslim scholar who speaks up for moderate Sunni sufism, a sufism which is based on the doctrine of the asceticism of the Qur'an, Prophetic traditions, and the tradition of his companions. He succeeded in purifying Sufism from various deviations, and harmonizing Sufism with sharia, and making it